Small-scale industry matters: industrialization and occupational structure in Turkey between 1927 and 1945 - Küçükbaşlar, Berkay. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2015., 2015)
This study aims to evaluate the significance of the small-scale manufacturing in Turkey’s history of industrialization both quantitatively and qualitatively by using the occupational data and the secondary sources. In Anatolia, there is much evidence on the existence and importance of small-scale producers throughout the nineteenth and twentieth centuries. However, the studies that handle this evidence is usually far from being comprehensive or systematic. On the other hand, there is a considerable amount of valuable information in demographic records, especially in national censuses. This can be analyzed in the context of economic history. Including this dataset in historical analyses and arguing on the relative significance of the small-scale industry constitutes the two main bases of this study. By doing this, it is aimed to reach a long-term, geographical and computational understanding on the nature of industrial production in Turkey. The weaving and clothing industries are two of the most specific examples as they were the pioneer branches of industry. In the international economic history literature, especially regarding weaving and clothing, there are various accounts that examine the innate coexistence of handwork and factory production. The notion of industry does not necessarily refer to a mechanized production; that is, in the context of Turkey, etatist industrialization. It is a necessity to look beyond factory production. This study combines this way of thinking with the available occupational data for the early periods of Republican Turkey. Keeping in mind that this should be done in longer periods, the results show that in certain provinces of western, central and eastern Anatolia, the concentration of weaving and clothing population cannot be explained with a simple scheme of modern industrialization. Further, as the most striking case, Denizli is examined more closely. It is seen that the industrial production pattern of this area was determined by strong local elements such as geography and production culture.
Keywords: Turkey -- Industry -- History.